Reducing foreign language anxiety through repeated exposure to a customizable VR public speaking application - Park, Seonjeong; Carlisle, Damaris D. E.; Cheng, Zimu; Gillies, Marco; Pan, Xueni (Frontiers in Virtual Reality, 2025)
This study investigated how repeated use of a customizable immersive virtual reality (VR) public speaking application could alleviate Foreign Language Anxiety (FLA) in English language learners, specifically native East Asian speakers. The goal was to explore how VR can serve as a tool to reduce FLA and enhance confidence in public speaking. Thirteen participants completed two blocks, each comprising three VR-based public speaking presentations. Participants customized their VR experience by selecting audience size, environment (classroom vs. conference room), and their avatar. Data collection included pre- and post-FLA questionnaires, Big Five personality traits, gaze tracking, performance evaluations, and semi-structured interviews. Results showed a significant reduction in FLA scores after six VR sessions. Behavioral evaluations indicated improved speech clarity, fluency, and confidence. Qualitative findings revealed different customization strategies, with some participants opting for challenging settings (e.g., larger audiences) and others preferring “safe” environments. Correlation analysis showed that introverted participants experienced greater FLA reduction. The study highlights VR’s potential as a flexible tool for language learning and professional skill development, allowing users to manage anxiety and practice public speaking in a controlled, customizable setting. This research uniquely integrates customizable VR features with FLA reduction strategies, linking anxiety reduction to personality traits and demonstrating VR’s potential for personalized learning and anxiety management.